Contemporary patterns of the management of truncus arteriosus (primary versus staged repair): outcomes from the Japanese National Cardiovascular Database. (30th July 2021) - Ota, Noritaka; Tachimori, Hisateru; Hirata, Yasutaka; Miyata, Hiroaki; Suzuki, Takaaki; Uchita, Shunji; Takamoto, Shinichi; Izutani, Hironori
Abstract: OBJECTIVES: Although primary repair in early infancy has for decades been the prevalent strategy for management of truncus arteriosus (TA), recent concerns about the levels of morbidity and mortality have led to consideration of a staged surgical approach. Our goal was to describe recent patterns of management, to characterize patients who underwent primary or staged repair and to evaluate risk factors associated with operative mortality in a contemporary multicentre cohort. METHODS: In the Japanese Cardiovascular Surgery Database, we identified all cases of TA undergoing an initial surgical procedure from 2008 to 2018. Operative mortality was defined as death within 30 days of an operation or in-hospital death regardless of the length of hospital stay. The hospital volume was defined by the average volume of TA repairs per year. RESULTS: The total number of patients undergoing initial surgery for TA was 286. Sixty-eight (24%, 68/286) underwent primary repair (primary repair group). The remaining 218 (76%, 218/286) underwent initial bilateral pulmonary artery banding as part of a planned staged approach (staged repair group). One hundred sixty-two patients out of 218 initially banded patients underwent the repair of TA during this study period. Concomitant diagnoses in the entire cohort included interrupted aortic arch repair in 36 patients and truncal valve regurgitation in 32. No centres handling an average of ≥2 truncus cases/year of the repair of TA were identified in this cohort. A total of 30% (85/286) of the cases were performed at centres that handled an average of ≥1 and <2 cases/year. The remaining 70% were at centres with <1 case/year. Overall, 37 patients (12.9%; 37/286) died. The operative mortality rates in the primary and staged repair groups were similar: that for the primary repair group was 16.2% (11/68) versus 11.9% for the staged repair group (26/218; P = 0.41). With multivariable logistic regression analysis, the factors most strongly associated with operative mortality were preoperative heart failure requiring catecholamine support (odds ratio, 4.18; 95% confidence interval 1.96–8.96) and the repeat bilateral pulmonary artery banding (odds ratio, 3.89; 95% confidence interval 1.08–14.07). CONCLUSIONS: The staged repair of TA has emerged as the preferred option for surgical timing at most of the centres participating in the Japanese Cardiovascular Surgery Database. The management outcomes of the patients with TA were favourable, even for the patients at low-volume centres. Abstract : Surgical repair of truncus arteriosus (TA) remains challenging.